Implementation of Performance Management on PT Philti Jaya Bintang - Leni Ariyanti; Vandi Verdiansyah; Muhammad Rozaki; Rahayu Sri Winastit; Satriadi Satriadi (Journal of Management and Informatics, 2023)
The purpose of this study is to evaluate the performance management strategies and practices implemented in the company and their impact on the productivity and success of the organization. The research method involves employee surveys and analysis of performance management-related documents. The results showed that PT Philti Jaya Bintang has adopted a performance management approach that focuses on individual performance measurement, skill development, and recognition of employee contributions. The research also identifies potential areas for improvement in the implementation of performance management, such as expanding employee development programs and improving communication between management and work teams. Although there are still challenges that need to be overcome, efforts to implement performance management at PT Philti Jaya Bintang have had a positive impact on employee productivity and engagement.